"Alexa, Am I pregnant?": A content analysis of a virtual assistant's responses to prenatal health questions during the COVID-19 pandemic. Issue 3 (March 2021) - Schindler-Ruwisch, Jennifer; Palancia Esposito, Christa
Highlights: Disruption in prenatal care is an opportunity to utilize mhealth to support patients. Amazon Alexa's responses were not credible in answering common pregnancy questions. Virtual assistants rendering evidence-based replies are valuable supplements to care. Virtual assistants, like Alexa, cannot replace consultations with health providers. Abstract: Objective: To elucidate whether Amazon's virtual assistant, Alexa, provides evidence-based support as a supplement to provider-facilitated prenatal care, during the COVID-19 pandemic. Methods: Using a conceptual content analysis approach, a query of 40 questions, relating to all phases of pregnancy, was collected from Alexa by two independent investigators, using two unique devices, over a one-week period between May 20, 2020 and May 27, 2020. Alexa's responses were matched to the evidence-based content from the American College of Obstetricians and Gynecologists (ACOG) and reviewed by a Certified Nurse Midwife for completeness and currency. Results: Of the 40 questions asked of Alexa, it was unable to answer 14 questions (35%). A total of 21 out of the 40 responses (52%) were not evidence-based and three COVID-specific questions (about 1%) were answered incorrectly or insufficiently. Four questions (10%) were answered accurately. Conclusion: Alexa was largely unable to provide evidence-based answers to commonly asked pregnancy questions and, in many cases, supplied inaccurate, incomplete, or completely unrelated answers that could further confuse health consumers. Practice Implications: Ensuring that mobile health (mhealth) tools, such as Amazon Alexa, are evidence-based and credible in answering common prenatal questions has important implications for this pandemic and future consumer needs.